Utilisation of Android Learning Video Application in Improving Student Achievement - Nur, Rezeki; Wahyuni, Erna; Gusniasari, Rosianna; Guilin, Xie; Salim, Yeffriansjah (World Psychology, 2023)
Android is a device that cannot be separated from education and learning in the current 5.0 era, for this reason educational institutions must have high enthusiasm in increasing the learning of android video applications to improve student achievement. The purpose of this study is that educators and students can utilize android learning video applications in improving student achievement in learning. This research was conducted with a quantitative method survey model, namely researchers distributed questionnaires using google form to educators and students. The results of this study explain that the android learning video application can be an alternative by educators in an effort to improve student achievement. To see an increase in student achievement through android learning videos, there needs to be training and development for educators and students, because android competition will be tighter in the future. Researchers have research limitations in conducting this android utilization survey because it does not cover all educational institutions, for that researchers hope that future researchers will conduct surveys with the addition of educational institutions and better ways.